Analysis of the effect of disclosure Corporate Social Responsibility (CSR) against tax avoidance - Astuti, Dwi; Dinarjito, Agung (Educoretax, 2024)
This research explores the relationship between Corporate Social Responsibility (CSR) and tax avoidance. CSR is seen as a social responsibility that reflects a company's compliance with stakeholder expectations, while tax avoidance is often considered an opportunistic act to maximize profits. This research uses a qualitative approach with a systematic literature review method (Systematic Literature Review/SLR) and uses the PRISMA method. The literature used is publications published from 2021 to 2024. This research aims to identify the relationship between Corporate Social Responsibility (CSR) disclosure and tax avoidance practices. Even though there are research that concludes there is no significant influence between CSR disclosure and tax avoidance practices, The results of the literature review show that most studies state a negative relationship between CSR disclosure and tax avoidance practices. In addition, other research finds a positive relationship because company size strengthens the influence of CSR on tax avoidance with a significant and beneficial effect. This research provides a theoretical contribution to existing literature by exploring the relationship between CSR disclosure and tax avoidance.